2019
DOI: 10.1002/jbio.201960120
|View full text |Cite
|
Sign up to set email alerts
|

Development of highly reliable SERS‐active photonic crystal fiber probe and its application in the detection of ovarian cancer biomarker in cyst fluid

Abstract: Conventionally Surface‐enhanced Raman spectroscopy (SERS) is realized by adsorbing analytes onto nano‐roughened planar substrate coated with noble metals (silver or gold) or their colloidal nanoparticles (NPs). Nanoscale irregularities in such substrates/NPs could lead to SERS sensors with poor reproducibility and repeatability. Herein, we demonstrate a suspended core photonic crystal fiber (PCF) based SERS sensor with extremely high reproducibility and repeatability in measurement with a relative SD of only 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 58 publications
(61 reference statements)
0
19
0
Order By: Relevance
“…the core were modified by Ag NPs through self-assembly, which ensured that a large number of hot spots could increase the SERS enhancement effect and a high enhancement factor of 1.3 × 10 9 . Experimental results confirmed that the sensor could detect ceftriaxone in real-time with a low detection limit of 10 -6 M. Recently, by modifying fluid channels around the core of SCF with Au NPs in self-assembly manner, Beffara's research group designed and fabricated an excellent in-fiber SERS sensing platform with superior reproducibility and repeatability of 1.5% and 4.6%, [332] as shown in Figure 49. The structural advantages of SCF ensured large active area and enhanced SERS signal.…”
Section: Structures and Sensing Applicationsmentioning
confidence: 74%
See 1 more Smart Citation
“…the core were modified by Ag NPs through self-assembly, which ensured that a large number of hot spots could increase the SERS enhancement effect and a high enhancement factor of 1.3 × 10 9 . Experimental results confirmed that the sensor could detect ceftriaxone in real-time with a low detection limit of 10 -6 M. Recently, by modifying fluid channels around the core of SCF with Au NPs in self-assembly manner, Beffara's research group designed and fabricated an excellent in-fiber SERS sensing platform with superior reproducibility and repeatability of 1.5% and 4.6%, [332] as shown in Figure 49. The structural advantages of SCF ensured large active area and enhanced SERS signal.…”
Section: Structures and Sensing Applicationsmentioning
confidence: 74%
“…First, the receptor molecules with strong Raman activity are used to modify the antibody to achieve the detection of biomarkers. [332] Second, we can modify the SERS substrate with some probe molecules with strong Raman activity such as GOD and malachite green isothiocyanate (MGITC). Then, according to the change of the SERS spectrum caused by the quantitative binding between these probe molecules and the target analytes, highly sensitive detection of weak Raman active molecular can be achieved.…”
Section: Sensing Principlementioning
confidence: 99%
“…Previously we have found that for the anchored configuration, 1X concentration of 60 nm Au NPs provides optimum SERS enhancement [34]. In the current study, we anchored the Au NPs inside the SuC-PCFs with 0.9 µm, 1.4 µm and 3.5 µm core and we compared their SERS response to the best concentration of Au NPs in injected configuration, respectively.…”
Section: Comparison Between Injected and Anchored Configurationsmentioning
confidence: 84%
“…The different solutions were prepared so that the concentration of ATP was constant among all samples, ie 1 mM. In our previous study [34], we easily detected nM concentrations of ATP and we demonstrated the linearity response of the SuC-PCFs for concentration range from 1 µM to 1 mM. Here, we used 1 mM ATP because we wanted to easily detect the SERS intensity even with very low concentration of Au NPs.…”
Section: Injection and Anchoring Of Nps And Analytementioning
confidence: 99%
See 1 more Smart Citation